Apoptosis of peripheral blood mononuclear cells in patients with sepsis - Jadali Zohreh; Amiri Mohammad; Ravanbakhsh Massoud (Wolters Kluwer Medknow Publications, 2010)
Context: Recent investigations into the pathogenesis of sepsis reveal an important role for apoptosis. The present study was designed in order to assess the peripheral blood mononuclear cells′ (PBMCs) apoptosis and the plasma levels of molecules associated with apoptosis belonging to tumor necrosis factor-alpha (TNF-α)/tumor necrosis factor type-1 receptor (TNFR I) pathway in patients with sepsis. Patients and Methods: Twenty-two patients with sepsis and 20 healthy subjects were included in the study. The percentage of PBMCs′ apoptosis was examined using annexin-V at the time of blood draws (0 time). PBMCs were incubated for 24 hour at 37°C in medium (spontaneous apoptosis) and in the presence of TNF-α. After incubation, the percentage of apoptotic cells was counted. Plasma levels of TNF-α and soluble TNFR I (sTNFR I) were also measured by enzyme linked immunosorbent assay (ELISA). Results: PBMCs of patients showed a higher proportion of apoptotic cells than PBMCs of controls at 0 time. After 24 hour incubation, spontaneous apoptosis of PBMCs was nearly as high as that of TNF induced apoptosis. Compared with healthy volunteers, patients with sepsis had elevated levels of TNF-α and sTNFR I. Conclusions: The data indicate that a higher fraction of PBMCs was undergoing apoptosis in vivo in patients than controls. Enhanced in vitro apoptosis has also been observed in patients with sepsis, suggesting that a greater number of mononuclear cells in the peripheral circulation of patients are preprogrammed in vivo to undergo apoptosis. The circulating levels of both TNF-α and sTNFR I from patients were significantly higher (P < 0.001) than controls. The increase in levels of TNF-α is proportional to that of sTNFR I (r = 0.908), indicating that sTNFR I may have a protective effect in the early stage of sepsis.